A novel method for redefining language ecology and endangerment in Nigeria : – towards a geospatial solution (Journal of the Digital Humanities Association of Southern Africa, 2022)
Being a multilingual and multicultural nation, Nigeria is blessed with over 525 languages (Blench, 2014) from four different language families. The sheer number of indigenous languages makes an interesting tapestry! Unfortunately, not much attention has been paid to the study of our indigenous languages, with all the abundant prospects. This paper is a work in progress and a recently funded research project by the Tertiary Education Trust Fund (TETFund) of Nigeria, to rescue language endangerment in Nigeria by redefining the ecology of languages through geospatial technologies; concentrating on those languages located in the southern part of Nigeria, and scalable to other regions of Nigeria and beyond. The main objective of the project is to implement a location-aware infrastructure or framework that functions proactively in real-time, for enhanced language ecology, and precise visualization of the language’s vitality status for each language spoken in the region under study. The project draws a multidisciplinary team consisting of linguists and language experts, computational scientists, and geographical information system (GIS) specialists, to examine our language ecology through practical fieldwork and integrate same into a geospatial framework for the purpose of revitalizing our indigenous languages and making them readily available. This research project is therefore significant as it will not only provide a cooperative solution for advancing our understanding of the spatial pattern that describes language ecology, but also provide an early appraisal of the degree of vitality and endangerment in relation to factors such as social and cultural changes. The immediate impact is the prompt revitalization of our indigenous languages and the development of an effective language policy to strengthen our local heritage.
Keywords: Nigerian languages; endangerment status; geo-linguistic database; geospatial framework; language ecology app; location- based system